Evaluation of a health-related intervention to reduce overweight, obesity and increase employment in France and the United Kingdom: a mixed-methods realist evaluation protocol - Sophia D. Amenyah; Jane Murphy; Lee-Ann Fenge (BMC, 2021)
Abstract Background Obesity, overweight and unemployment are interlinked, with debilitating effects on mortality, health, wellbeing and quality of life. Existing interventions to reduce overweight, obesity and unemployment have addressed these challenges independent of each other with limited success. The Adding to Social capital and individual Potential In disadvantaged REgions (ASPIRE) project will develop an innovative model using a combination of skills training and health and wellbeing interventions to improve health, wellbeing, quality of life and reduce overweight, obesity and unemployment in England and France. The aim of this paper is to outline the protocol for evaluating the ASPIRE project to examine the effectiveness of the intervention and clarify the mechanisms and contextual factors which interact to achieve outcomes. Methods A mixed-method realist evaluation using a single-group before-and-after design will be used. The evaluation will consist of development of an initial programme theory, theory validation and refinement using quantitative and qualitative data to understand the causal mechanisms, contexts of implementation and their interactions that result in outcomes observed in ASPIRE. Primary outcomes that will be assessed are change in body weight and body mass index, reemployment and a rise on the ASPIRE participation ladder. The ASPIRE participation ladders consists of a series of 5 steps to engage participants in the project. The first step on the ladder is joining an ASPIRE hub with paid employment as the final step on the ladder. Secondary outcomes will be physical activity, diet quality, self-efficacy and health-related quality of life. Both quantitative and qualitative approaches are appropriate in this study because the use of validated questionnaires and objective measures will demonstrate how much the intervention addressed outcomes related to weight loss and reemployment and the qualitative data (photovoice) will provide insights into the contexts and experiences that are unique to participants in the project. Discussion The results from this evaluation will provide an understanding of how a model of health-related interventions which improve health, wellbeing and maintenance of a healthy lifestyle could reduce overweight, obesity and unemployment. The findings will enable the adaptation of this model for effective implementation in different contexts and circumstances. Trial registration ISRCTN registry: Study ID: ISRCTN17609001 , 24th February 2021 (Retrospectively registered).